PEMBERIAN BANTUAN HUKUM OLEH ADVOKAT SEBAGAI IMPLEMENTASI OFFICIUM NOBILE DALAM SISTEM PERADILAN PIDANA - Adri Indra (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Act number 18 Year 2003 article (1 and 2), the advocate's profession is a person who giveslegal services, both within and outside the Court meet the requirements based on theprovisions of this Act. The actions of the irregularities committed by persons-personsadvocate that damage the image of the profession of advocate today, should not be abarrier that stops the execution of the noble profession of advocates themselves. Startingfrom dotted background problems that have been described above, it can be raised twoprincipal issues, namely: 1. How is the grant of legal aid by advocates as implementationof the officium nobile in the criminal justice system? 2. What are the obstacles found byadvocates in the granting of legal aid as officium nobile in the criminal justice system toanswer both of the above problems in this research is descriptive research. The approachused in this study are normative juridical approach as the main approach that is supportedby empirical juridical approach. The granting of legal assistance by advocates asimplementation of the officium nobile in the criminal justice system have not done wellbecause: still found irregularities committed by advocates. Restricting factors that affectthe implementation of the grant of legal aid can be divided into four factors: First the legalsubstance of the factors (legal substance use). the structure of the law (legal structure). theculture of the law (legal culture). The fourth.